PENGARUH ASIMETRI INFORMASI KEUANGAN, PENAWARAN SAHAM PERDANA, DISCRETIONARY ACCRUAL TERHADAP TINGKAT RETURN SAHAM PADA PERUSAHAAN GO PUBLIK (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2011-2015) - Sri Sinta Wardani; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2017)
The study was conducted to examine the effect of information asymmetry, initial stock offering value and discretionary accrual to retun stock. Population in this research is a manufacturing company listed on Indonesia Stock Exchange 2013-2015, sample selection is done by purposive sampling method and yield 58 sample research. The results showed that simultaneously asymmetry of information, initial public offering and descretion accrual effect on stock return. Partially information asymmetry has a significant effect on stock return, while the value of initial stock offering and descretionary partially accrual has no significant effect on stock return.